2020
DOI: 10.12659/msm.924602
|View full text |Cite
|
Sign up to set email alerts
|

Differential Metabolic Pathways and Metabolites in a C57BL/6J Mouse Model of Alcoholic Liver Disease

Abstract: The present study was supported by the National Natural Science Foundation of China [81873570] and grants for the 4 th Excellent Scientific Research of QNBJRC from Anhui Medical University [2013500023]. This study was carried out at the Basic SPF Animal Laboratory of Anhui Medical University. Animal ethics approval number: LLSC20180145 Background:Alcoholic liver disease (ALD), an important cause of acute or chronic liver injury, results from binge drinking or long-term alcohol consumption. To date, there is n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
0
8
1
Order By: Relevance
“…A recent study suggests that potential pathways associated with alcoholic liver injury, including the D-glutamine, D-glutamate, cysteine, and methionine metabolisms in the liver [16]; but we did not find the same metabolisms in the serum, which may be because the serum or tissues, animal species, alcohol dose, and duration were different. In the present study, chronic alcohol consumption was elevated PG levels compared to the Con group about 1.3-fold, however, MWF (50, 100, and 200 mg/kg) or silymarin (200 mg/kg) supplementation were further increased PG levels by 1.5-, 2.2-, 1.6-, 1.6-fold, respectively, compared with the EtOH group.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…A recent study suggests that potential pathways associated with alcoholic liver injury, including the D-glutamine, D-glutamate, cysteine, and methionine metabolisms in the liver [16]; but we did not find the same metabolisms in the serum, which may be because the serum or tissues, animal species, alcohol dose, and duration were different. In the present study, chronic alcohol consumption was elevated PG levels compared to the Con group about 1.3-fold, however, MWF (50, 100, and 200 mg/kg) or silymarin (200 mg/kg) supplementation were further increased PG levels by 1.5-, 2.2-, 1.6-, 1.6-fold, respectively, compared with the EtOH group.…”
Section: Discussioncontrasting
confidence: 99%
“…Metabolomics provides a means of characterizing metabolic phenotypes and is used to identify metabolic disorders and discover biomarkers that can be used to diagnose or monitor diseases [15]. Ma et al [16] recently reported that 35 metabolites were significantly altered in the liver of alcohol diet compared to the isocaloric control diet mice. Dong et al [17] also demonstrated that chronic alcohol consumption induced significant alteration of serum FAs and bile acids by metabolic pathway analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The NADPH produced by this pathway also serves as a reducing agent for anabolic pathways, such as fatty acid synthesis, and to regenerate reduced glutathione in response to oxidative stress [ 49 , 50 ]. Alcohol’s impact on the PPP is not well characterized, with suggestions that alcohol inhibits the PPP in non-pregnant alcoholics and in alcoholic liver disease [ 51 , 52 , 53 ]. The brain content of PPP intermediates is reduced in rats exposed to excessive alcohol drinking [ 54 ], suggesting that effects are conserved across organs.…”
Section: Discussionmentioning
confidence: 99%
“…The first, succinic acid, may be reflective of generalized alcohol exposure due to the formation of this metabolite during alcoholic fermentation [ 136 ], but is a relatively novel hit considering a lack of studies on the topic. The second, Guanosine Monophosphate Inosine, has been identified in a pathway analysis screening of metabolite dysfunction in an animal model of alcoholic liver disease [ 137 ] but otherwise also remains a novel hit. Further work on these two potential corollaries may therefore unveil their biological importance in mediating the effects of prenatal alcohol exposure on the developing brain.…”
Section: Discussionmentioning
confidence: 99%